Eddie Izzard [videorecording (DVD)] : dress to kill - Jordan, Larry, 1934-; Izzard, Eddie (Distributed by Anti-, 1998)
Executive transvestite Eddie Izzard takes his show to San Francisco to give a brief history of pagan and Christian religions, the building of Stonehenge, the birth of the Church of England and of Western empires, and the need for a European dream.